Socio-Demographic and Environmental Risk Factors Associated with Superficial Fungal Infections in School-Aged Children (The Insight, 2025)
Background: Superficial fungal infections are common among school-aged children, especially in low- and middle-income countries. These infections, though often not life-threatening, can lead to significant discomfort, stigma, and school absenteeism. This study aimed to assess the socio-demographic and environmental risk factors associated with superficial fungal infections in children. Methods & Materials: This cross-sectional, descriptive study was conducted at the outpatient department of the Department of Dermatology and Venereology, Mugda Medical College Hospital, Dhaka, Bangladesh, from January 2024 to June 2024. A total of 385 children aged 5-17 years with superficial fungal infections were included in this study. Results: The majority of participants (38.18%) were between 9-12 years old, and 54.29% were females. Most children were from lower socioeconomic backgrounds (57.92%) and lived in urban areas (69.35%). Common environmental exposures included sharing towels or bedding (60.26%) and wearing synthetic clothes (46.23%).. Tinea corporis is the most prevalent type of superficial fungal infection (57.66%), followed by tinea cruris (42.86%), tinea faciei (20.52%), and tinea capitis (16.62%). Older children (11–17 years) were more likely to belong to lower socioeconomic class (p = 0.001), poor personal hygiene (p < 0.0001), have contact with animals (p < 0.001), wear synthetic clothing (p < 0.001), and experience frequent sweating (p < 0.001). Conclusion: Socioeconomic status, family size, hygiene practices, and environmental exposures significantly influence the risk of superficial fungal infections in school-aged children. Targeted public health interventions focusing on hygiene education and environmental improvements could help reduce the burden of these infections in vulnerable pediatric populations.
Keywords: Superficial fungal infections; School-aged children; Socio-demographic factors; Hygiene; Risk factors